Cost and fare estimation for the urban bus transit system of Santiago - Batarce, Marco; Galilea, Patricia (Congreso Chileno de Ingeniería de Transporte, 2013)
In this paper, we estimate the cost function of bus operators of Transantiago and the Budget balance fare to contribute technically to the discussion on the level of subsidies needed for transit system of Santiago. We estimate the cost function and an aggregate demand model. Our results show that there are economies of density and the budget-balance fare (type Ramsey price) is higher than the actual bus fare, suggesting that subsidies are justified. Nevertheless, we estimate that for the current (December 2011) fare the subsidy should be 40% lower than the one determined by the Government. On the other hand, we estimate that for such level of subsidy the optimal fare should be only 50% of the current fare.